Auto dos anfitriões e O homem duplicado: diferentemente iguais - Souza, Eli Fernandes de (2009)
This work consists of the analysis of Auto dos Anfitriões, by Luís Vaz de Camões, which was written in 1587, and The Double, by José Saramago, published in 2002. These works approach the theme of the double a recurrent subject in literature since primordial times and they present different manners of constituting duplicity. In the analyzed corpus, the dialogue is established firstly with the myth of Amphitryon, and, though less intensely, with other western culture myths. The analyses have as theoretical support Bakhtin studies on dialogism which is seen as a constitutive principle of language and Sigmund Freud researches on the double in his article The uncanny . Sustained by these seminal studies and contributions by other experts on the subject, we aim at investigating how the theme of the double is treated in each work and to which directions the identity crisis point; analyzing the characters discourse, so as to observe how the I acts before the other; and, at last, examining the mechanisms to which the narrative resorts in the confrontation of these discursive subjects. The study of these works shows that in ancient literature the loss of individuality, which is an intrinsic factor to the theme of the double, does not predominantly assume dramatic dimensions, as it happens in modern literature, which frequently reach tragic outcomes. Trough the work of Olympian gods the conflict is both established and ended in the text by Camões, therefore the identity crisis is not aggravated, but attenuated before the jest, the humorous tone, while, due to human solitude, individualism and modern man s lack of references, the ontological crisis in The Double occurs within the hero s existence, undermining his defenses to, eventually, destroy him.